The fatal strain : on the trail of avian flu and the coming pandemic - Sipress, Alan. (New York, N.Y. : Penguin Books, 2010)
When a highly lethal strain of avian flu broke out in Asia in 2003 and raced westward, Sipress, as a reporter for the Washington Post, tracked the virus across nine countries, watching its secrets elude the world's brightest scientists and most intrepid disease hunters. --Back cover.
The revenge of Begu Ganjang -- A visitation from outer space -- The elephant and the lotus leaf -- Into the volcano -- Livestock revolution -- From a single spark -- Cockfighting and karma -- Sitting on fire -- The secret call -- Let's go save the world -- The lights go out at seven -- Peril on the floodplain.
Includes bibliographical references (p. 339-378) and index.
Keywords: Avian influenza -- Popular works